Comparison of outcome between nonoperative and operative treatment of medial epicondyle fractures - Grahn, Petra; Hämäläinen, Tero; Nietosvaara, Yrjänä; Ahonen, Matti (Acta Orthopaedica, 2020)
Background and purpose — Controversy exists regarding the optimal treatment for displaced medial epicondyle fractures. We compared the results of nonoperative and operative treatment and calculated the incidence of medial epicondyle fractures in the pediatric census population. Patients and methods — 112 children under 16 years old who sustained > 2 mm displaced fracture of the medial epicondyle were treated in our institution between 2014 and 2019. 80/83 patients with 81 non-incarcerated fractures were available for minimum 1-year follow-up. 41 fractures were treated with immobilization only, 40 by open reduction and internal fixation, according to the preference of the attending surgeon. Outcome was assessed at mean 2.6 years (1–6) from injury with different patient-reported outcome measures. Elbow stability, range of motion, grip strength, and distal sensation were registered in 74/80 patients. Incidence was calculated for 7- to 15-year-olds. Results — Nonoperatively treated children had less pain according to the PedsQL Pediatric Pain Questionnaire (3 vs. 15, p = 0.01) with better cosmetic outcome (VAS 95 vs. 87, p = 0.007). There was no statistically significant difference between the groups in respect of QuickDASH, PedsQL generic core scale, Mayo Elbow Performance Score, grip strength, carrying angle, elbow stability, or range of motion (p > 0.05). All 41 nonoperatively treated children returned to pre-injury sports; of the surgically treated 6/40 had to downscale their sporting activities. The incidence of displaced (> 2 mm) fractures of the medial epicondyle in children aged 7–15 years was ≥ 3:100,000. Interpretation — Displaced fractures of the medial humeral epicondyle in children heal well with 3–4 weeks’ immobilization. Open reduction and screw fixation does not improve outcome.